White matter abnormalities and illness severity in major depressive disorder - James H. Cole; Christopher A. Chaddock; Anne Farmer; Katherine J. Aitchison; Andrew Simmons; Peter McGuffin; Cynthia H.Y. Fu (2012)
White matter abnormalities have been implicated in the aetiology of major depressive disorder; however, the relationship between the severity of symptoms and white matter integrity is currently unclear.To investigate white matter integrity in people with major depression and healthy controls, and to assess its relationship with depressive symptom severity.Diffusion tensor imaging data were acquired from 66 patients with recurrent major depression and a control group of 66 healthy individuals matched for age, gender and IQ score, and analysed with tract-based spatial statistics. The relationship between white matter integrity and severity of depression as measured by the Beck Depression Inventory was examined.Depressive illness was associated with widespread regions of decreased white matter integrity, including regions in the corpus callosum, superior longitudinal fasciculus and anterior corona radiata, compared with the control group. Increasing symptom severity was negatively correlated with white matter integrity, predominantly in the corpus callosum.Widespread alterations in white matter integrity are evident in major depressive disorder. These abnormalities are heightened with increasing severity of depressive symptoms.